PENGARUH KUALITAS PELAYANAN PADA KEPUASAN NASABAH - Jeliria Karniawati; Seno Andri; Chalid Sahuri (JIANA ( Jurnal Ilmu Administrasi Negara ), 2017)
Effect of Service Quality on Customer Satisfaction. This study aims to determine and analyze the effect of service quality on customer satisfaction in the Work Area of Regional Office of BRI Pekanbaru. The instrument used for data collection is a questionnaire. The population of this research is Bank BRI customers located in the Working Area of BRI Pekanbaru Regional Office which accumulated until 31 December 2015 amounted to 77,750 people. The sample in this study based on the formula taro yamane obtained 100 people. Data analysis techniques use simple linear regression analysis. The results show that service quality has a significant direct and positive influence on customer satisfaction. This study concludes that the better service quality applied to customers in the Work Area of BRI Pekanbaru Regional Office, the better the customer satisfaction. Direct contribution given quality of service on customer satisfaction is equal to 54,6%, while the rest 45,4% influenced by other factor.